Implementation of mappings between the description logic and the binary relational data model on the RDF level - Chystiakova, I.S. (Проблеми програмування, 2020)
This paper is dedicated to the data integration problem. In article the task of practical implementation of mappings between description logic and a binary relational data model is discussed. This method was formulated earlier at a theoretical level. A practical technique to test mapping engines using RDF is provided in the current paper. To transform the constructs of the description logic ALC and its main extensions into RDF triplets the OWL 2-to-RDF mappings are used. To convert RDB to RDF graph, the R2R Mapping Language (R2R ML) was chosen. The mappings DL ALC and its main extensions to the RDF triplets are described in the publication. The mapping of the DL axioms into an RDF triplet also is considered in the publication. The main difficulties in describing DL-to-RDF transformations are given in the corresponding section. For each constructor of concepts and roles a corresponding expression in OWL 2 and its mapping into the RDF triplet. A schematic representation of the resulting RDF graph for each mapping is created. The paper also provides an overview of existing methods that relate to the use of RDF when mapping RDB to ontology and vice versa. Ця публікація присвячена проблемі інтеграції даних, а саме – створенню механізму відображень між дескриптивною логікою та бінарною реляційною моделлю даних. Метод створення відображень був запропонований та описаний на теоретичному рівні. З метою його практичної перевірки, у поточній публікації пропонується метод реалізації відображень між дескриптивною логікою та бінарною реляційною моделлю даних за допомогою RDF. У роботі наведено огляд існуючих методів та засобів перетворення реляційних баз даних в онтологію та навпаки за допомогою RDF. Було сформульовано постановку задачі реалізації відображень та розглянуто відображення дескриптивної логіки ALC, її основних розширень, а також аксіоматики у RDF-трійки. У статті відзначено ряд складнощів при відображенні дескриптивної логіки на рівень RDF.